Two-Dimensional and Three-Dimensional Evaluation of the Deformation Relief; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna (2017, 2017)
Title screen